Analysis of Disaster Management Systems in Tsunami Shelter Management in Padang City - Tirza Haqia Purnama; Egi Zulfarayani; Edi Hasymi; Roni Ekha Putera (Jurnal Ilmiah Ekotrans & Erudisi, 2025)
Padang City, Indonesia, faces near-field tsunami risk where evacuation time is severely limited, making vertical evacuation shelters critical life-safety infrastructure. This study analyzes the disaster management system underpinning tsunami shelter management in Padang using a qualitative case study design. Data were drawn from policy and planning documents, the BPBD Padang shelter inventory (2019), and the BPBD tsunami evacuation plan map (2025), and analyzed through thematic analysis with source triangulation. Results indicate four systemic issues: (1) fragmented shelter definitions and incomplete inventories that weaken capacity planning; (2) a pronounced readiness assurance gap, where large nominal capacity (~53,874 people) coexists with feasibility-testing status recorded as “not yet conducted” for key shelters; (3) partial operational integration between shelters, evacuation routes, warning devices, and routine drills; and (4) governance challenges arising from a multi-owner shelter portfolio requiring clear accountability, access guarantees, and sustainable maintenance. The study contributes a readiness assurance lens that distinguishes nominal shelter availability from verified operational readiness and offers actionable implications: establishing a unified shelter registry, institutionalizing feasibility evaluation and recertification, strengthening end-to-end integration with evacuation operations, and formalizing governance instruments for privately owned shelters. These findings highlight that effective tsunami shelter management depends on governing shelters as safety-critical socio-technical systems rather than static assets.